Traces of gold : California's natural resources and the claim to realism in western American literature - Witschi, Nicolas S., 1966- (University of Alabama Press, 2002)
Broadening our understanding of what constitutes "realism," Nicolas Witschi artfully demonstrates the linkage of American literary realism to the texts, myths, and resources of the American West. From Gold Rush romances to cowboy Westerns, from hard-boiled detective thrillers to nature writing, the American West has long been known mainly through hackneyed representations in popular genres. But a close look at the literary history of the West reveals a number of writers who claim that their works represent the "real" West. As Nicolas Witschi shows, writers as varied as Bret
Keywords: American literature -- California -- History and criticism.; Authors, American -- Homes and haunts -- California.; California -- Intellectual life.; Natural resources -- California.; California -- In literature.; Realism in literature.; Nature in literature.; Écrivains américains -- Résidences et lieux familiers -- Californie.; Nature dans la littérature.; Réalisme dans la littérature.; Californie -- Dans la littérature.; Californie -- Vie intellectuelle.; Ressources naturelles -- Californie.; LITERARY CRITICISM -- American -- General.; American literature; Authors, American -- Homes and haunts; Intellectual life; Literature; Natural resources; Nature in literature; Realism in literature; California; Criticism, interpretation, etc.